Vitamin B6 Acquisition and Metabolism in Schistosoma mansoni - Da’dara, Akram A.; Elzoheiry, Manal; El-Beshbishi, Samar N.; Skelly, Patrick J. (Frontiers in Immunology, 2021)
Schistosomes are parasitic platyhelminths that currently infect >200 million people globally. The adult worms can live within the vasculature of their hosts for many years where they acquire all nutrients necessary for their survival and growth. In this work we focus on how Schistosoma mansoni parasites acquire and metabolize vitamin B6, whose active form is pyridoxal phosphate (PLP). We show here that live intravascular stage parasites (schistosomula and adult males and females) can cleave exogenous PLP to liberate pyridoxal. Of the three characterized nucleotide-metabolizing ectoenzymes expressed at the schistosome surface (SmAP, SmNPP5 and SmATPDase1), only SmAP hydrolyzes PLP. Heat-inactivated recombinant SmAP can no longer cleave PLP. Further, parasites whose SmAP gene has been suppressed by RNAi are significantly impaired in their ability to cleave PLP compared to controls. When schistosomes are incubated in murine plasma they alter its metabolomic profile - the levels of both pyridoxal and phosphate increase over time, a finding consistent with the action of host-exposed SmAP acting on PLP. We hypothesize that SmAP-mediated dephosphorylation of PLP generates a pool of pyridoxal around the worms that can be conveniently taken in by the parasites to participate in essential, vitamin B6-driven metabolism. In addition, since host PLP‐dependent enzymes play active roles in inflammatory processes, parasite-mediated cleavage of this metabolite may serve to limit parasite-damaging inflammation. In this work we also identified schistosome homologs of enzymes that are involved in intracellular vitamin B6 metabolism. These are pyridoxal kinase (SmPK) as well as pyridoxal phosphate phosphatase (SmPLP-Ph) and pyridox(am)ine 5’-phosphate oxidase (SmPNPO) and cDNAs encoding these three enzymes were cloned and sequenced. The three genes encoding these enzymes all display high relative expression in schistosomula and adult worms suggestive of robust vitamin B6 metabolism in the intravascular life stages.